Diagnoza w postępowaniu karnym wobec nieletnich przestępców we Francji - Perska-Gradowska, Paulina (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The purpose of the article is to analyse the role of diagnosis in criminal proceedings against juvenile offenders. Firstly, the conditions of juvenile criminal liability in France are presented. It is emphasised that the basic condition is being able to discern the act committed. The second part concerns the measures ordered by a judge for minors to gather information about the minor, their family situation and functioning environment. In the conclusion, the role of diagnosis in criminal proceedings is described. It is worth emphasising that the diagnosis in the French system provides support for a judge and conditions the juvenile criminal liability.
Keywords: nieletni; odpowiedzialność karna; roztropność